Probing the Anti-Corrosion Behavior of X65 Steel Underwater FSW Joint in Simulated Seawater - Ma, Gang; Gao, Hui; Sun, Chong; Gu, Yanhong; Zhao, Jie; Fang, Zewei (Frontiers in Materials, 2022)
To detect the corrosion resistance of a friction stud welding (FSW) joint in simulated seawater (3.5 wt% NaCl solution approximately replaced seawater), pulse electrochemical deposition method was used for electroplating Ni coating with different duty ratios (50%, 80% and 100%) on the surface of FSW joint. The microstructure and surface structure of the coating were observed by micro-spectroscopy and other characterization methods. The corrosion behavior of the coating was analyzed by means of macroscopic electrochemical testing. The local corrosion law of joint surface and coating surface defects were innovatively explored by using micro-zone electrochemical scanning system. The coating characterization results showed that as the duty ratio continues to increase, the coating surface becomes denser and smoother, the corrosion pits and cracks gradually reduce, and the corrosion products such as Fe2O3, Fe3O4 and FeOOH are generated. The results of macroscopic electrochemical experiment showed that the coating with 100% duty ratio has the most positive self-corrosion potential, the lowest corrosion current density and the maximum polarization resistance. The scanning vibrating electrode technique (SVET) results showed that the corrosion current density in the defect area is higher than that in the coating area, and the maximum corrosion current density decreases with the increase of duty ratio. The localized electrochemical impedance spectroscopy (LEIS) results showed that the localized impedance at the welded zone (WZ) was the largest, and with the increase of the pulse duty ratio, the impedance diffusion in the defect area was decreasing.